Motor capacity and its relationship with some indicators Albaiukinmetekih and performance of the wheel of human skill - م.م. ابتهال رياض عمران; أ.د. انتصار كاظم عبد الكريم (الرياضة المعاصرة)
The research problem is represented in the weakness of reliance on the role of some motor abilities (flexibility, balance and compatibility) in biomechanical indicators and the performance of a large number of gymnastics skills, including the skill of the human wheel, in addition to the lack of reliance on the use of video imaging of the skill in order to analyze its path and identify its weaknesses.